2021
DOI: 10.1111/nph.17601
|View full text |Cite
|
Sign up to set email alerts
|

A triple threat: the Parastagonospora nodorum SnTox267 effector exploits three distinct host genetic factors to cause disease in wheat

Abstract: Parastagonospora nodorum is a fungal pathogen of wheat. As a necrotrophic specialist, it deploys effector proteins that target dominant host susceptibility genes to elicit programmed cell death (PCD). Here we identify and functionally validate the effector targeting the host susceptibility genes Snn2, Snn6 and Snn7.We utilized whole-genome sequencing, association mapping, gene-disrupted mutants, gain-of-function transformants, virulence assays, bioinformatics and quantitative PCR to characterize these interact… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 68 publications
0
31
0
2
Order By: Relevance
“…New Phytologist K2PP effector interaction for further study of this class of effectors. Outram et al (2020) presented the crystal structure of SnTox3, which was used by the protein structuring server PHYRE2 to model the 3D structure of both SnTox5 and SnTox267 (Richards et al, 2021). PHYRE2 was able to model 98% of the structure of the mature SnTox5 with 100% confidence, whereas it was able to model only 35% of the mature SnTox267 with 92.6% confidence, which suggests structural homology between SnTox3 and SnTox5 and, to a lesser extent, SnTox3 and SnTox267.…”
Section: Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…New Phytologist K2PP effector interaction for further study of this class of effectors. Outram et al (2020) presented the crystal structure of SnTox3, which was used by the protein structuring server PHYRE2 to model the 3D structure of both SnTox5 and SnTox267 (Richards et al, 2021). PHYRE2 was able to model 98% of the structure of the mature SnTox5 with 100% confidence, whereas it was able to model only 35% of the mature SnTox267 with 92.6% confidence, which suggests structural homology between SnTox3 and SnTox5 and, to a lesser extent, SnTox3 and SnTox267.…”
Section: Researchmentioning
confidence: 99%
“…To date, nine such interactions have been identified, including SnToxA-Tsn1 (Friesen et al, 2006;Faris et al, 2010), SnTox1-Snn1 (Liu et al, 2004;Shi et al, 2016), SnTox2-Snn2 (Friesen et al, 2007), SnTox3-Snn3-B1 (Friesen et al, 2008), SnTox3-Snn3-D1 (Zhang et al, 2011;Zhang et al, 2021), SnTox4-Snn4 (Abeysekara et al, 2009), SnTox5-Snn5 (Friesen et al, 2012), SnTox6-Snn6 (Gao et al, 2015) and SnTox7-Snn7 (Shi et al, 2015). Even though SnTox2, SnTox6 and SnTox7 were initially hypothesized to be three different effectors that targeted three separate sensitivity genes, Richards et al (2021) recently showed that these three effectors were in fact the same protein, which was designated as SnTox267. Owing to the number of characterized interactions, the wheat-P. nodorum system is recognized as a model for the study of necrotrophic specialist pathogens (Oliver et al, 2012;Faris & Friesen, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, eight Snn-SnTox interactions are known [17]. In addition to the three main interactions Snn1-SnTox1, Snn3-SnTox3, and Tsn1-SnToxA, several other interactions have been identified, such as Snn2-SnTox2, Snn4-SnTox4, Snn5-SnTox5, Snn6-SnTox6 and Snn7-SnTox7 [18][19][20][21][22][23]. The effect of each Snn-SnTox interaction is incomplete and is complemented by other interactions.…”
Section: Expression Of Necrotrophic Effectors Determines the Virulence Of The S Nodorum Isolatementioning
confidence: 99%
“…nodorum- wheat pathosystem. These are ToxA- Tsn1 [ 13 , 14 ], Tox1- Snn1 [ 15 , 16 ], Tox267- Snn2 / Snn6 / Snn7 [ 17 ], Tox3- Snn3B1 / Snn3D1 [ 18 , 19 ], Tox4- Snn4 [ 20 ], Tox5- Snn5 [ 21 ] and Tox2A- Qsnb . cur–2AS1 [ 22 ].…”
Section: Introductionmentioning
confidence: 99%